Dry-mixed thin anti-crack waterproof plaster mortar and preparation method thereof
Patent Information
- Application Number
- CN202511506930.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-10-21
AI Technical Summary
本公开技术方案解决了现有技术保水不足、界面粘结薄弱及开裂控制不彻底的问题,适用于高层建筑外墙保温系统防护层
[0028]根据本公开的实施例,步骤b中低速混合(<200rpm)能够保持纤维的完整性,避免纤维在混合过程中断裂或损伤,从而最大化纤维的增强效果。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a dry-mixed thin-film crack-resistant and waterproof plastering mortar and its preparation method. Background Technology
[0002] Dry-mixed thin-film crack-resistant and waterproof plastering mortar is a dry mixture made from ordinary silicate cement, dry fine aggregate, mineral admixtures, and functional additives, mixed in a specific ratio. Water is added according to the ratio before use. Dry-mixed thin-film crack-resistant and waterproof plastering mortar is divided into two types according to its application. Type II is used on the surface of the insulation layer, composite with alkali-resistant fiberglass mesh to form a crack-resistant and waterproof protective layer, with an average thickness not exceeding 8mm.
[0003] The existing Type II dry-mixed thin-layer crack-resistant plastering mortar has the following defects: 1. Relying solely on cellulose ethers results in low water retention; 2. The insulation board substrate was not optimized, and the substrate was not fixed during the tensile bond strength test, which could not guarantee that the failure occurred in the insulation layer; 3. The anti-cracking agent relies on pore filling, with a minimum cracking index of 0.15 mm; Therefore, there is an urgent need for an environmentally friendly Type II mortar that simultaneously meets the requirements of high water retention, high interfacial adhesion, and crack prevention. Summary of the Invention
[0004] To address the problems in related technologies, this disclosure provides a dry-mixed, thin-film, crack-resistant, and waterproof plastering mortar and its preparation method. The mortar uses cement, quartz sand, silane-modified carbon fiber, a nano-clay-alginate composite water-retaining system, redispersible latex powder, hydroxypropyl methylcellulose ether, and MgO-type expanding agent as main raw materials, prepared through a fully aqueous phase process. Its water retention rate is ≥99.0%, and its 14-day tensile bond strength with EPS / XPS insulation board is ≥0.25 MPa with failure occurring in the insulation layer, and its cracking index is 0 mm. This disclosed technical solution solves the problems of insufficient water retention, weak interfacial bonding, and incomplete crack control in existing technologies, and is suitable for the protective layer of high-rise building exterior wall insulation systems.
[0005] In a first aspect, this disclosure provides a dry-mixed, thin-film, crack-resistant, and waterproof plastering mortar, comprising, by weight: 120-150 parts cement; 550-650 parts of quartz sand; 0.8-2.4 parts of silane-modified carbon fiber, wherein the silane-modified carbon fiber is carbon fiber that has undergone surface grafting treatment with γ-aminopropyltriethoxysilane, and the grafting rate is ≥90%; 5-11 parts of nano-clay-alginate composite water-retaining system, wherein the composite water-retaining system is composed of sodium alginate and calcium ions cross-linked to form a hydrogel network and coated with nano-attapulgite, wherein sodium alginate is 1-3 parts and nano-attapulgite is 4-8 parts. 2-4 parts of redispersible latex powder; Hydroxypropyl methylcellulose ether, 0.1-0.5 parts; 5-10 parts of expanding agent.
[0006] In this disclosure, quartz sand (40-70 mesh) serves as the basic aggregate component, forming the main structure of the mortar together with cement and nano-clay-alginate composite. Using 40-70 mesh quartz sand provides an appropriate particle size distribution, ensuring good workability and strength of the mortar. This particle size range allows quartz sand to form a dense skeletal structure with the cement paste, reducing porosity and improving the mortar's density and strength. Simultaneously, an appropriate particle size distribution also helps improve the mortar's water retention and crack resistance. In practical applications, the amount and particle size distribution of quartz sand can be fine-tuned according to different construction requirements. For example, for applications requiring higher strength, 620-650 parts of quartz sand can be used, with an appropriate increase in the proportion of finer particles (60-70 mesh) to improve the mortar's density and strength.
[0007] In this disclosed method, sodium alginate (ALG) crosslinks with calcium ions to form a three-dimensional hydrogel network with a water retention rate as high as 99.8%, effectively preventing rapid water loss. Nano-attapulgite (AT) possesses a large specific surface area and layered structure, enabling it to adsorb free water and delay the release of heat of hydration, further improving water retention performance. AT nanosheets are interwoven within the cement pores, forming a physical barrier that blocks the propagation of microcracks, achieving a cracking index of 0 mm.
[0008] In this disclosed method, γ-aminopropyltriethoxysilane (KH550) forms a graft layer on the surface of carbon fibers, and its amino groups can react with the ester bonds on the surface of the EPS / XPS insulation board. This chemical bonding significantly enhances the interfacial bonding force between the fiber and the insulation board, ensuring a bond strength ≥0.20 MPa and that failure occurs in the insulation layer.
[0009] The amount of silane-modified carbon fiber added is 0.8-2.4 parts, preferably 0.8-1.5 parts, and more preferably 1.8-2.4 parts. Specifically, the amount of silane-modified carbon fiber is increased to 1.8-2.4 parts in high-stress areas such as the building top, corners, and around openings, and carbon fibers of three lengths (3 mm, 6 mm, and 9 mm) are mixed in a 1:2:1 mass ratio to form a multi-scale fiber network. Preferably, 0.5-1.5 wt% nano-silica with a particle size of 10-50 nm is additionally added in high-stress areas to strengthen the interfacial transition zone.
[0010] Applying dry-mixed thin-film crack-resistant and waterproof plaster mortar to the exterior wall insulation system of high-rise buildings presents a unique technical challenge. Due to increased building height, the exterior walls face stronger wind pressure and temperature variations, leading to increased interfacial stress between the plaster layer and the insulation board. This stress concentration is particularly pronounced at the building's top and corner areas. Although silane-modified carbon fiber improves interfacial bond strength, localized detachment or cracking may still occur in these high-stress areas. This problem is primarily caused by the uneven distribution of wind loads and thermal stress unique to high-rise buildings, as well as the stress concentration effect caused by the building's geometry. Conventional uniform reinforcement methods are insufficient to effectively address this localized high-stress condition; therefore, further optimization tailored to the specific needs of high-rise buildings is required.
[0011] To address the interfacial bonding problem in high-stress areas of exterior wall insulation systems for high-rise buildings, the amount of silane-modified carbon fiber was increased, and a gradient-distributed fiber reinforcement structure was introduced into the mortar to achieve targeted reinforcement of high-stress areas.
[0012] The specific implementation method is as follows: 1. Fiber Gradient Distribution Design: Based on the building height and geometry, the exterior wall is divided into different stress zones. The amount of silane-modified carbon fiber is increased in high-stress areas (such as the top, corners, and around openings) to create a gradient distribution. For example, the amount of carbon fiber is kept constant at 0.8-1.5 parts, preferably 1.2 parts, in standard areas, while increasing to 1.8-2.4 parts in high-stress areas.
[0013] 2. Multi-scale fiber composite: Introducing carbon fibers of different lengths, such as combinations of 3mm, 6mm, and 9mm, into high-stress regions. This multi-scale fiber network can more effectively disperse stress and prevent crack propagation at different scales.
[0014] 3. Localized reinforcement with nanomaterials: In high-stress areas, the amount of nano-silica added can be increased from 0.5% to 1-1.5%. Nano-silica can fill the micropores between cement hydration products, enhance the structure of the interfacial transition zone, and improve the bond strength and durability of local areas.
[0015] This gradient enhancement optimization scheme works by precisely controlling the number and size of fibers, as well as the localized addition of nano-silica materials, to form a stronger interfacial structure in high-stress areas. The multi-scale fiber network provides a comprehensive stress transfer and dispersion mechanism. The addition of nanomaterials further optimizes the microstructure, improving interfacial bonding and durability.
[0016] This optimization scheme can effectively solve the interface bonding problem in local high-stress areas of high-rise building exterior wall insulation systems, significantly improving the overall performance and durability of the system.
[0017] In this disclosure, the length of the silane-modified carbon fiber is 3-9 mm, preferably 6 mm.
[0018] In this disclosed method, the addition of an MgO-type expansive agent can compensate for the shrinkage of the mortar during the hardening process, further reducing the risk of cracking. During hydration, MgO slowly generates Mg(OH)₂, expanding in volume by approximately 120%. This micro-expansion effect can counteract the shrinkage stress during cement hydration, thereby reducing the formation of microcracks. In practical applications, the dosage of the expansive agent can be adjusted according to the specific formula, typically between 5 and 10 parts. For example, during winter construction, because low temperatures slow down the hydration rate of MgO, the dosage can be appropriately increased to 8-9 parts to ensure sufficient expansion effect.
[0019] In this disclosure, redispersible latex powder (VAE) forms a flexible polymer film in the mortar, enhancing its toughness and deformability. This flexible film can absorb some stress and reduce the formation of microcracks. Simultaneously, VAE improves the adhesion between the mortar and the substrate, particularly at the interface with the insulation board, where it synergizes with silane-modified carbon fibers to further enhance overall bond strength. In practical applications, the dosage can be adjusted according to different environmental conditions and performance requirements. For example, when constructing in high-humidity environments, the VAE dosage can be slightly increased to 3.5-4.0 parts to improve the mortar's waterproofing performance and durability.
[0020] In this disclosure, hydroxypropyl methylcellulose ether (HPMC) exhibits excellent water retention and thickening effects, assisting the main water-retaining system in maintaining the workability of the mortar. It forms a water-soluble gel, slowing down water evaporation and extending the mortar's workability. Simultaneously, HPMC improves the mortar's viscosity and thixotropy, facilitating even application and reducing sagging during construction. In practical applications, the dosage of HPMC can be fine-tuned according to ambient temperature and humidity. For example, in hot, dry summers, the dosage of HPMC can be appropriately increased to 0.4-0.5 parts to enhance water retention and prevent cracking caused by rapid water loss in the mortar.
[0021] According to embodiments of this disclosure, the nano-clay-alginate composite water-retaining system is prepared through the following steps: Nano-attapulgite clay is dispersed in deionized water to form a 5-10 wt% suspension; Sodium alginate was added at 25±5℃ and 200-400 rpm with stirring to achieve a sodium alginate concentration of 1-3 wt%. Slowly add 2-3 wt% CaCl2 solution to carry out ionic cross-linking; After cross-linking, spray drying is performed to obtain microspheres with a particle size of 50-100 μm.
[0022] According to embodiments of this disclosure, the method for preparing the silane-modified carbon fiber includes: The carbon fiber was placed in a mixture of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1) and acid-washed at 60-80℃ for 1-2 hours. After washing with water until neutral, immerse in 3-7 wt% γ-aminopropyltriethoxysilane in an ethanol-water solution and reflux at 80°C for 2-3 h. After removal, the carbon fibers are dried at 100-110℃ to obtain silane-modified carbon fibers with a surface grafting rate of ≥90%.
[0023] According to embodiments of this disclosure, the quartz sand has a particle size of 40-70 mesh, and the mass ratio of quartz sand to cement is 4.0-5.5:1.
[0024] According to embodiments of this disclosure, the expanding agent is lightly calcined MgO.
[0025] According to embodiments of this disclosure, the glass transition temperature (Tg) of the redispersible latex powder is 0-10°C, and the minimum film-forming temperature is 0-5°C.
[0026] According to embodiments of this disclosure, the viscosity of the hydroxypropyl methylcellulose ether is 40,000-60,000 mPa·s. Viscosity measurement is performed by preparing a 2% aqueous solution and measuring the viscosity at 20°C.
[0027] In a second aspect, this disclosure provides a method for preparing the dry-mixed thin-film crack-resistant and waterproof plastering mortar described in any one of the first aspects, comprising the following steps: Step a: Dry mix cement, quartz sand, expanding agent, and hydroxypropyl methylcellulose ether at 100-200 rpm for 2-3 minutes; Step b: Add silane-modified carbon fiber, redispersible latex powder and nano-clay-alginate composite water-retaining system, and continue mixing at <200 rpm for 3-5 min to avoid fiber damage; Step c: Add water at a water-cement ratio of 0.18-0.22 and stir for 3-5 minutes until homogeneous; Step d: Allow to stand for 10-15 minutes before proceeding with the application.
[0028] According to embodiments of this disclosure, low-speed mixing (<200 rpm) in step b can maintain the integrity of the fibers, prevent the fibers from breaking or being damaged during the mixing process, thereby maximizing the reinforcing effect of the fibers.
[0029] According to embodiments of this disclosure, in step b, the mixing temperature is controlled at 15-30°C and the relative humidity is 40-70%.
[0030] According to the embodiments of this disclosure, the ambient humidity is maintained at ≥60% and the temperature at 5-35℃ for 24 hours after step d.
[0031] The dry-mixed, thin-film, crack-resistant, and waterproof plastering mortar provided in this disclosure has the following significant advantages: (1) Introducing a nano-clay-alginate composite water retention system, in which sodium alginate and calcium ions crosslink to form a hydrogel network, and combined with nano-attapulgite to construct a composite water retention system, thereby improving the water retention rate.
[0032] (2) Silane coupling agent is used to modify carbon fiber. γ-aminopropyltriethoxysilane is used to modify the surface of carbon fiber to improve the interfacial bonding strength with the insulation board.
[0033] (3) Cracking index of 0 mm, completely solving the problem of microcracks.
[0034] (4) All-aqueous process, zero VOC emissions.
[0035] It should be understood that the above general description and the following detailed description are exemplary and explanatory only, and are not intended to limit this disclosure. Detailed Implementation
[0036] The present invention is further illustrated below by way of examples, but it should be understood that these specific examples are not intended to limit the scope of the invention in any way. It should be noted that, unless otherwise specified, the raw materials used in the following examples are all commercially available.
[0037] Example 1: Raw material ratio, by weight: 135 parts cement, 600 parts 40-70 mesh quartz sand, 1.2 parts silane-modified carbon fiber (γ-aminopropyltriethoxysilane grafting rate 92%, length 6mm), 6.0 parts nano-attapulgite, 2.0 parts sodium alginate, 3.0 parts redispersible latex powder (Tg=5℃), 0.3 parts hydroxypropyl methylcellulose ether (viscosity 50000 mPa·s), and 7 parts lightly calcined MgO.
[0038] Preparation steps: 1. Dry mix cement, quartz sand, lightly calcined MgO, and hydroxypropyl methylcellulose ether at 150 rpm for 2 min; 2. Add silane-modified carbon fiber, redispersible latex powder, and nano clay-alginate composite (nano attapulgite and sodium alginate crosslinked with CaCl2 and spray-dried, particle size 80μm), and continue mixing for 3-5 min at 180 rpm, 25℃, and 60% humidity. 3. Add water at a water-cement ratio of 0.20, stir for 5 minutes until uniform, let stand for 15 minutes before construction.
[0039] Example 2: Raw material ratio, by weight: 140 parts cement, 580 parts 40-70 mesh quartz sand, 1.0 part silane-modified carbon fiber (γ-aminopropyltriethoxysilane grafting rate 90%, length 6mm), 5.0 parts nano-attapulgite, 1.5 parts sodium alginate, 2.5 parts redispersible latex powder (Tg=3℃), 0.4 parts hydroxypropyl methylcellulose ether (viscosity 45000 mPa·s), and 8 parts lightly calcined MgO.
[0040] The preparation steps are the same as in Example 1.
[0041] Example 3: Raw material ratio, by weight: 150 parts cement, 650 parts 40-70 mesh quartz sand, 0.8 parts silane-modified carbon fiber (γ-aminopropyltriethoxysilane grafting rate 91%, length 5.5 mm), 4.0 parts nano-attapulgite, 1.0 part sodium alginate, 4.0 parts redispersible latex powder (Tg=8℃), 0.1 parts hydroxypropyl methylcellulose ether (viscosity 40000 mPa·s), and 10 parts lightly calcined MgO.
[0042] The preparation steps are the same as in Example 1.
[0043] Example 4: Raw material ratio, by weight: silane-modified carbon fiber increased to 2 parts, and 3 mm, 6 mm and 9 mm carbon fibers were introduced and mixed in a 1:2:1 ratio, the remaining components were the same as in Example 1.
[0044] The preparation steps are the same as in Example 1.
[0045] The construction area in Example 4 is a high-stress area, such as the top and corner areas of a building. The tested bond strength is 0.30 MPa and the cracking index is 0 mm.
[0046] Comparative Example 1: The carbon fiber was not treated with silane, and the proportions of the remaining raw materials and the preparation steps were the same as in Example 1.
[0047] Comparative Example 2: The nano-clay-alginate complex was replaced with an equal amount of hydroxypropyl methylcellulose ether, and the remaining raw material ratios and preparation steps were the same as in Example 1.
[0048] Comparative Example 3: The raw material ratio is the same as in Example 1. In the preparation steps, the mixing speed in step 2 is 400 rpm, and the remaining steps are the same as in Example 1.
[0049] Performance test method description: Water retention rate: The water retention performance of mortar is tested according to JGJ / T 70.
[0050] Tensile bond strength: As specified in 4.3.1 of DG / TJ 08-2433A-2023, the molding thickness is 3mm and the test age is 14d. Water resistance and freeze-thaw resistance are as specified in GB / T 29906 and the test age is 28d.
[0051] Cracking index: as specified in Appendix A of T / SCIA 004-2024.
[0052] Water impermeability: The test shall be conducted in accordance with Appendix C of JG / T 158, and the test substrate shall be a 5mm thick non-removable thermal insulation template.
[0053] 2-hour consistency loss rate: Conducted according to GB / T 25181, where the consistency test instrument should be a Vicat apparatus conforming to GB / T1346. The standard consistency value range during the test should be 45mm to 50mm, and the mortar mixture should contain no less than 300g.
[0054] 28-day compressive strength: as specified in JGJ / T 70.
[0055] Compression-to-flexural ratio: as specified in GB / T 29906.
[0056] The test results of Examples 1-3 and Comparative Examples 1-3 are shown in the table below:
[0057] As shown above, Example 1 achieved a water retention rate of 99.7% (compared to only 90.2% in Comparative Example 2), confirming the high water-locking capacity of the nano-clay-alginate composite system. All examples had a cracking index of 0 (compared to 3.5 mm in Comparative Example 2), as the composite system forms a physical barrier to block microcrack propagation. Example 1 showed a bonding strength of 0.28 MPa with the insulation board, with all failures occurring in the insulation layer. Comparative Example 1 (unmodified fiber) showed a 35.7% decrease in strength, demonstrating that the silane coupling agent enhances interfacial interaction through chemical bonding. Comparative Example 3, using high-speed mixing, resulted in fiber damage leading to a 5.9% decrease in compressive strength and an increase in the cracking index to 0.4 mm, highlighting the necessity of low-speed mixing (<200 rpm) for maintaining fiber integrity.
[0058] The above description is merely a preferred embodiment of this disclosure and an explanation of the technical principles employed. Those skilled in the art should understand that the scope of the invention involved in this disclosure is not limited to technical solutions formed by specific combinations of the above-described technical features, but should also cover other technical solutions formed by arbitrary combinations of the above-described technical features or their equivalents without departing from the inventive concept. For example, technical solutions formed by substituting the above-described features with (but not limited to) technical features disclosed in this disclosure that have similar functions.
Claims
1. A dry-mixed, thin-film, crack-resistant, and waterproof plastering mortar, characterized in that, By weight, it comprises: 120-150 parts cement; 550-650 parts of quartz sand; 0.8-2.4 parts of silane-modified carbon fiber, wherein the silane-modified carbon fiber is carbon fiber that has been grafted onto the surface of γ-aminopropyltriethoxysilane, with a grafting rate ≥90%; the length of the silane-modified carbon fiber is 3-9 mm. 5-11 parts of nano-clay-alginate composite water-retaining system, wherein the composite water-retaining system is composed of sodium alginate and calcium ions cross-linked to form a hydrogel network and coated with nano-attapulgite, wherein sodium alginate is 1-3 parts and nano-attapulgite is 4-8 parts. 2-4 parts of redispersible latex powder; Hydroxypropyl methylcellulose ether, 0.1-0.5 parts; 5-10 parts of expanding agent, wherein the expanding agent is lightly calcined MgO; The nano-clay-alginate composite water-retaining system is prepared through the following steps: Nano-attapulgite clay is dispersed in deionized water to form a 5-10 wt% suspension; Sodium alginate was added at 25±5℃ and 200-400 rpm with stirring to achieve a sodium alginate concentration of 1-3 wt%. Slowly add 2-3 wt% CaCl2 solution to carry out ionic cross-linking; After cross-linking, spray drying is performed to obtain microspheres with a particle size of 50-100 μm.
2. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The preparation method of the silane-modified carbon fiber includes: The carbon fiber was placed in a mixture of concentrated sulfuric acid and concentrated nitric acid (volume ratio 3:1) and acid-washed at 60-80℃ for 1-2 hours. After washing with water until neutral, immerse in 3-7 wt% γ-aminopropyltriethoxysilane in an ethanol-water solution and reflux at 80°C for 2-3 h. After removal, the carbon fibers are dried at 100-110℃ to obtain silane-modified carbon fibers with a surface grafting rate of ≥90%.
3. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The quartz sand has a particle size of 40-70 mesh, and the mass ratio of quartz sand to cement is 4.0-5.5:
1.
4. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The glass transition temperature (Tg) of the redispersible latex powder is 0-10℃, and the minimum film-forming temperature is 0-5℃.
5. The dry-mixed thin-film crack-resistant and waterproof plastering mortar according to claim 1, characterized in that, The viscosity of the hydroxypropyl methylcellulose ether is 40,000-60,000 mPa·s.
6. A method for preparing the dry-mixed thin-film crack-resistant and waterproof plastering mortar according to any one of claims 1-5, characterized in that, Includes the following steps: Step a: Dry mix cement, quartz sand, expanding agent, and hydroxypropyl methylcellulose ether at 100-200 rpm for 2-3 min; Step b: Add silane-modified carbon fiber, redispersible latex powder and nano-clay-alginate composite water-retaining system, and continue mixing at <200 rpm for 3-5 min to avoid fiber damage; Step c: Add water at a water-cement ratio of 0.18-0.22 and stir for 3-5 minutes until homogeneous; Step d: Allow to stand for 10-15 minutes before proceeding with the application.
7. The method according to claim 6, characterized in that, In step b, the mixing temperature is controlled at 15-30℃ and the relative humidity is 40-70%.
8. The method according to claim 6, characterized in that, After step d, maintain an ambient humidity of ≥60% and a temperature of 5-35℃ for 24 hours.
Citation Information
Patent Citations
Heat preserving crack resistant mortar for exterior wall
CN101195529A
Water-preserving agent for preventing water leakage of dry or semi-dry farmland
CN1243858A